The study of the microstructures of clay sediments: a case study of marly sediments from N. Péloponnèse - ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΥ, Τ. Α.; ΤΣΩΛΗ - ΚΑΤΑΓΑ, Π.; ΚΟΥΚΗΣ, Γ. Χ.; ΚΟΝΤΟΠΟΥΛΟΣ, Ν. (Bulletin of the Geological Society of Greece, 2018)
This paper deals with the systematic study of the microstructural characteristics of clay sediments. These characteristics which are closely connected to the physical and mechanical character of the sediments, are concerned with: a)the structural constituents, b)the microporosity and c)the structural bonds of the sediments. For the determination of the structural characteristics of clay sediments the Scanning Electron Microscope (SEM) and the Optical Microscope are widely used with a supplementary mineralogical analysis of sediment components and the determination of several physical and mechanical characteristics. The observations under the microscope must be focused on the distribution of mineralogical facies and micropores, on the size and shape of clay (micro-)aggregates, as well as on the kind of authigenic facies (e.g. micrite, sparry calcite) which play the role of cementing material. The proposed methodology was applied to the study of the microstructures of marly sediments from Northern Péloponnèse and the following types of microstructures were determined: a)matrix-skeletal, mixed type, coarse dispersed of low orientation, b)matrix, coagulative, medium dispersed of medium orientation and c)crystallized-cementated, fine or medium dispersed of low orientation.